Investigate the capability of INAA absolute method to determine the concentrations of 238U and 232Th in rock samples - I. A., Alnour; H., Wagiran; N., Ibrahim; S., Hamzah; Wee, Boon Siong; M. S., Elias (Springer Netherlands, 2014)
This work aimed to study the capability of INAA absolute method in determining the elemental concentration of 238U and 232Th in the rock samples. The INAA absolute method was implemented in PUSPATI TRIGA Mark II research reactor, Malaysian Nuclear Agency (NM). The accuracy of INAA absolute method was performed by analyzing the IAEA certified reference material (CRM) Soil-7. The analytical results showed the deviations between experimental and certified values were mostly less than 10 % with Z-score in most cases less than 1. In general, the results of analysed CRM Soil-7 show a good agreement between certified and experimental results which mean that the INAA absolute method can be used accurately for elemental analysis of uranium and thorium in various types of samples. The concentration of 238U and 232Th ranged from 1.77 to 24.25 and 0.88 to 95.50 ppm respectively. The highest value of 238U and 232Th was recorded for granite rock sample G17 of 238U and sample G9 of 232Th, whereas the lower value was 1.77 ppm of 238U recorded in sandstone rock and 0.88 ppm of 232Th for gabbro. Moreover, a comparison of the 238U and 232Th results obtained by the INAA absolute method shows an acceptable level of consistency with those obtained by the INAA relative method.